Seroepidemiological study of Neospora caninum in equids using c-ELISA in Erbil Province, Iraq - Jabar Aziz, Khalid; Mikaeel, Farhad Buzo; Azeez, Sarhang Hasan; Bilal, Samir Jawdat (Folia parasitologica, 2024)
Equine neosporosis is an intracellular protozoan disease with a global distribution, affecting a diverse range of warm-blooded animals. Neospora caninum Dubey, Carpenter, Speer, Topper et Uggla, 1988 is associated with foetal loss, neurological disease and abortion in equids. No information was available regarding equine N. caninum infection among equids in Iraq. Thus, the aim of this study was to determine the prevalence rate of N. caninum in equines by using a competitive enzyme-linked immunosorbent assay (c-ELISA). A total of 329 blood samples randomly selected from equines, comprising 268 horses and 61 donkeys were examined. The seroprevalence rate of N. caninum was determined as 46% (28/61) for donkeys and 24% (64/268) for horses. The prevalence of N. caninum indicated a significantly higher risk of infection in donkeys compared to horses (P < 0.001). However, the odds of N. caninum infection in draught equids were 8.2 times greater than other equids with a significant difference (P < 0.001). The current study revealed no significant differences in the prevalence of N. caninum across various genders, breeds, clinical statuses, disease histories and among equids that had contact with dogs. While outdoor feeding and mixed (grazing), showed a significant difference (P = 0.003) and (P = 0.75), respectively, in the presence of antibodies against N. caninum compared to indoor feeding (stable). Moreover, the odds of infection in equids with a history of late abortion were 4.8 times higher than those without such a history of abortion (2.20-10.56) with statistical significance (P < 0.001).
Keywords: protilátky protozoální; Male; Seroepidemiologic Studies; risk factors; séroepidemiologické studie; kokcidióza; prevalence; Antibodies, Protozoan; mužské pohlaví; ELISA; Coccidiosis; nemoci koní; seroprevalence; Neospora; Enzyme-Linked Immunosorbent Assay; Animals; Equidae; Iraq; ženské pohlaví; equines.; zvířata; Prevalence; Irák; koně; Female; Horse Diseases; Horses; Neosporosis